THE IMPACT OF STAKEHOLDER THEORY ON THE DEVELOPMENT OF SUSTAINABILITY REPORTING AND ITS STANDARDISATION - TYVONCHUK, Olena; TITOV, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides a comprehensive analysis of the evolution and implementation of stakeholder theory in sustainability reporting. The study traces the origins of stakeholder theory, outlines its fundamental assumptions, and distinguishes prominent scholars who significantly contributed to its development. Particular attention is paid to the analysis of two main branches of stakeholder theory: ethical (normative), which emphasises the inherent rights of all stakeholders and the principle of accountability, and managerial (instrumental), which considers stakeholders in terms of their ability to influence the company’s activities. A critical analysis of the impact of the ethical and managerial dimensions of the stakeholder theory on the formation of modern sustainability reporting standards is carried out. The study shows that GRI and ESRS mainly reflect an ethical approach, underscores the impact of a company on a wide range of stakeholders, and uses the concept of dual materiality. Conversely, IFRS S1 and S2, with their primary focus on the information needs of investors, are more in line with the managerial perspective, although they recognise the importance of the company’s interaction with all stakeholders in creating value. The article points out that the stakeholder theory serves as a fundamental theoretical basis for understanding corporate responsibility and the need for companies to take into account the interests of all stakeholders in their sustainability reporting practices. It is concluded that the theory plays a key role in the continuous development of reporting standards that ensure transparent and comprehensive disclosure of information about the impact of companies on society and the environment, taking due account of the diverse interests of all stakeholders.